2013
DOI: 10.1093/arclin/act032
|View full text |Cite
|
Sign up to set email alerts
|

Odor Identification Deficit Predicts Clinical Conversion from Mild Cognitive Impairment to Dementia Due to Alzheimer's Disease

Abstract: The aim of this study was to analyze the relationship between olfactory and cognitive functions in subjects affected by mild cognitive impairment (MCI) and to investigate whether olfactory deficits might reflect the likelihood of conversion from MCI to dementia. In this longitudinal study conducted on a sample of MCI outpatients, CA-SIT Smell Identification Test was administered to 88 MCI subjects and 46 healthy control subjects. MCI subjects have been divided into two groups, considering smell identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(82 citation statements)
references
References 43 publications
(39 reference statements)
4
77
0
1
Order By: Relevance
“…4 Deficits in OI precede impairment on olfactory threshold detection tasks 26 and remain after cognitive measures and odor detection deficits are controlled for, 5 suggesting a pathophysiologic process that originates near the central olfactory structures in the medial temporal lobe. 5,23,[27][28][29] Although the exact inception point of AD pathology in the olfactory system remains unknown, the disease course progressively involves 29 multiple levels of the olfactory system, 27,30 including peripheral structures such as the olfactory bulb and epithelium, as well as higher order olfactory pathways connected to cognitive processes. 25 Studies have shown greater OI deficits in patients with AD compared to those with vascular dementia, 31,32 suggesting that the site of vascular pathology may determine the type and severity of olfactory deficit, 33 with specific olfactory deficits observed only in patients whose corresponding olfactory structures sustained vascular damage, in contrast to the multiple-level impairment observed across the olfactory system in AD pathology.…”
Section: Resultsmentioning
confidence: 99%
“…4 Deficits in OI precede impairment on olfactory threshold detection tasks 26 and remain after cognitive measures and odor detection deficits are controlled for, 5 suggesting a pathophysiologic process that originates near the central olfactory structures in the medial temporal lobe. 5,23,[27][28][29] Although the exact inception point of AD pathology in the olfactory system remains unknown, the disease course progressively involves 29 multiple levels of the olfactory system, 27,30 including peripheral structures such as the olfactory bulb and epithelium, as well as higher order olfactory pathways connected to cognitive processes. 25 Studies have shown greater OI deficits in patients with AD compared to those with vascular dementia, 31,32 suggesting that the site of vascular pathology may determine the type and severity of olfactory deficit, 33 with specific olfactory deficits observed only in patients whose corresponding olfactory structures sustained vascular damage, in contrast to the multiple-level impairment observed across the olfactory system in AD pathology.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, in 88 patients with MCI, 47% of patients with low olfactory scores (,24) progressed to dementia in 2 years compared with 11% of patients with normal olfactory scores ($24). 29 The UPSIT and similar tests, with culturally appropriate modifications when needed, can be a useful predictor of cognitive decline and the transition to AD dementia across different ethnicities.…”
Section: Baseline Demographic and Clinical Measuresmentioning
confidence: 99%
“…In the present study, MMSE, which assessed cognitive function of the geriatric patients, showed significant positive correlation with discrimination and identification scores. As patients with severe cognitive dysfunction and Parkinson's disease are known to have olfactory dysfunction [18], and olfactory dysfunction could be an early symptom of neurodegenerative diseases such as Parkinson's disease and Alzheimer dementia [19], we excluded these patients from our study. Despite the exclusion of these patients, decreasing cognitive function scores correlated with decreasing discrimination and identification scores.…”
Section: Discussionmentioning
confidence: 99%